2019
DOI: 10.1016/j.clineuro.2019.02.022
|View full text |Cite
|
Sign up to set email alerts
|

Disability patterns over the first year after a diagnosis of epilepsy

Abstract: 2019) Disability patterns over the first year after a diagnosis of epilespy. Clinical Neurology and Neurosurgery, 179,[60][61][62][63][64][65] Objective: To determine the patterns and predictors of disability over the first 12 months after a diagnosis of epilepsy. Patients and methods: The Sydney Epilepsy Incidence Study to Measure Illness Consequences (SEISMIC) was a prospective, multicenter, community-based study of people with newly diagnosed epilepsy in Sydney, Australia. Disability was assessed using the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 50 publications
1
10
0
Order By: Relevance
“…After adjusting all the potential confounders, greater disability (the highest WHODAS score) was associated with increased odds of having neurological disorders when compared with lower disability (the lower WHODAS score) [OR = 1.30 (95% CI 1.02-1.66)]. Consistent with our finding a recent study found a significant and positive association between greater disability and increased risks of depression [47].…”
Section: Plos Onesupporting
confidence: 89%
“…After adjusting all the potential confounders, greater disability (the highest WHODAS score) was associated with increased odds of having neurological disorders when compared with lower disability (the lower WHODAS score) [OR = 1.30 (95% CI 1.02-1.66)]. Consistent with our finding a recent study found a significant and positive association between greater disability and increased risks of depression [47].…”
Section: Plos Onesupporting
confidence: 89%
“…Fourteen [7][8][9][10][11][12][13][14][15][16][17][18][19][20] were cohort studies and two 21,22 were randomized controlled trials. Three 13,18,19 studies considered first seizure cohorts exclusively (Table 1), eight 17,[23][24][25][26][27][28][29] considered newly diagnosed epilepsy cohorts exclusively (Table 2), and five 21,22,[30][31][32] considered both first seizure and newly diagnosed epilepsy cohorts (Table 3). Nine studies 17,19,[21][22][23]25,[28][29][30] excluded patients with any past psychiatric diagnosis, and six 17,21,[27][28][29]32…”
Section: Description Of Included Studiesmentioning
confidence: 99%
“…The 16 included studies used six different validated instruments to capture anxiety and depressive symptoms in first seizure and newly diagnosed epilepsy cohorts. This included the Hospital Anxiety and Depression Scale (HADS) in eight studies, 13,17,18,[23][24][25][26]31 Generalised Anxiety and Depression (GAD-7) instrument in four studies, 21,[27][28][29] Neurological Disorders Depression Inventory for Epilepsy (NDDIE) in four studies, 21,[27][28][29] the Beck Depression Inventory (BDI) in two studies, [30][31][32] Self-Rating Depression Scale (SRDS) in one study, 19 and Brief Depression Scale (BDS) in one study. 22 Relevant cutoff scores are summarized in Tables 1-3.…”
Section: Instrumentsmentioning
confidence: 99%
See 1 more Smart Citation
“…SEISMIC is registered on the Australia New Zealand Clinical Trial Registration database, and the protocol and main results are published [14][15][16][17]. In brief, people of all ages with a new diagnosis of epilepsy were identified and enrolled through a geographically based multi-site ascertainment process in Sydney, Australia from July 2008 to December 2013.…”
Section: Study Design and Patientmentioning
confidence: 99%